(untitled) (Comparative Professional Pedagogy, 2024)
The challenges of wartime have prompted Ukrainian researchers to seek the most effective methods for enhancing professional education, particularly professional training of future vocational education teachers. As a result, examining the leading European experience with content and language integrated learning (CLIL) in professional training programmes for future vocational education teachers is scientifically justified and necessary. It is found that the problem of using CLIL in professional training of future specialists is notably significant. In the context of globalization and European integration processes, future professionals must demonstrate high levels of foreign language competence and competitiveness in the international labour market. Leading European countries, including Germany, the Netherlands, Belgium, France and Spain, actively implement CLIL’s conceptual aspects in their training programmes. However, the specific features of these implementations, such as sectorality, strategies and approaches, assessment characteristics and material support, may vary. The main advantages and challenges of using CLIL in professional training of future vocational education teachers are identified. Based on leading European experiences, the most effective methods to enhance professional training through CLIL are substantiated. These methods include the development of integrated educational programmes, effective use of resources, differentiated instruction, systematic assessment and feedback, as well as reflective practice. Accordingly, relevant recommendations are proposed to improve professional training of future vocational education teachers in Ukraine by integrating key aspects of CLIL into curricula. It is defined that, by adopting these practices, future vocational education teachers can effectively employ CLIL to enhance both language and vocational learning, better preparing their students for success in global and multicultural work environments. Further research is aimed at analyzing the content of foreign language training for future vocational education teachers in developed countries.